Skin-to-skin contact and breastfeeding practices in Nigeria: a study of socioeconomic inequalities - Michael Ekholuenetale; Amadou Barrow; Amit Arora (BMC, 2022)
Abstract Background The effects of breastfeeding practices on children's health are undoubtedly of great interest. However, inequalities in breastfeeding practices and mother and newborn skin-to-skin contact (SSC) exist in many resource-constrained settings. This study examined the regional prevalence and socioeconomic inequalities in exclusive breastfeeding (EBF), early initiation of breastfeeding and SSC in Nigeria. Methods Data on 2936 infants under six months were extracted from the 2018 Nigeria Demographic and Health Survey (NDHS) to determine EBF. In addition, data on 21,569 children were analysed for early initiation of breastfeeding and SSC. Concentration index and curves were used to measure socioeconomic inequalities in EBF, early initiation of breastfeeding and SSC. Results The prevalence of EBF, early initiation of breastfeeding and SSC were 31.8, 44.2 and 12.1% respectively. Furthermore, Ogun state had the highest prevalence of EBF (71.4%); while Bayelsa state had the highest prevalence of SSC (67.8%) and early initiation of breastfeeding (96.2%) respectively. Urban dwellers had higher prevalence of EBF, SSC and early initiation of breastfeeding across household wealth quintile and by levels of mothers' education in contrast to their rural counterparts. We quantified inequalities in early initiation of breastfeeding, EBF, and SSC according to household wealth and maternal education. The study outcomes had greater coverage in higher household wealth, in contrast to the lower household wealth groups; early initiation of breastfeeding (concentration index = 0.103; p = 0.002), EBF (concentration index = 0.118; p < 0.001), and SSC (concentration index = 0.152; p < 0.001) respectively. Furthermore, early initiation of breastfeeding (concentration index = 0.091; p < 0.001), EBF (concentration index = 0.157; p < 0.001) and SSC (concentration index = 0.156; p < 0.001) had greater coverage among mothers with higher educational attainment. Conclusion Low prevalence and socioeconomic inequalities in early initiation of breastfeeding, EBF and SSC were identified. We recommend that health promotion programs targeted and co-designed with disadvantaged mothers are critical to meet global breastfeeding targets. Also, future researchers should conduct further studies especially clinical control trials and qualitative studies to unravel the possible reasons for differences in the indicators.